PROFIL HORMON ESTRADIOL 17β DAN INDUKSI HORMON OVAPRIM DALAM PEMIJAHAN BUATAN IKAN SELAIS (Ompok hypophthalmus Blkr) - Nasril Ismail; Usman M Tang; Henni Syawal (Fakultas Perikanan dan Kelautan, Universitas Riau, 2018)
The purpose of this study was analyze the amount of estradiol and tostesterone hormone in the body of the selais (O. hypophthalmus Blkr) fish the mature gonads and the number of ovaprim hormone doses used based on the amount of hormone in the fish body on ovulatory success and spawning of fish Selais. The study used a complete randomized design consisting of four treatments and three replicates consisting of controls, 0.05 mL / 100 grams of body weight, 0.07, mL / 100 gram body weight, 0.09 mL / 100 gram body weight and 0,11 mL / 100 gram body weight. The results showed that the concentrations of estradiol-17β hormone in blood ranged from 199.13 pg / mL to 236.28 pg / mL before and after ovulation of each treatment ranging from 273.97 pg / mL to 873.65 pg / mL and after ovulation ranged from 0.71 pg / mL to 1.78 pg / mL Whereas for other parameters obtained the results of the latency 11.27 ± 0.252 to 13.40 ± 1,95 hours, fecundity 1919 ± 0.546 to 3243 ± 0.420 grains, egg diameter after ovulation 1.32 ± 0.29 to 1.32 ± 0.29 mm, fertilization rate of 28.99±157 to 36.54±148 %, hatching rate of 40.79± 071 to 36.54±148 % and the survival rate 3 day 75.82 ± 047 to 84.53 ± 0.36 %.